Cost-effectiveness of surgical mask, N-95 respirator, hand-hygiene and surgical mask with hand hygiene in the prevention of COVID-19: Cost effectiveness analysis from Indian context - Bhavani Shankara Bagepally; Madhumitha Haridoss; Meenakumari Natarajan; Kathiresan Jeyashree; Manickam Ponnaiah (Elsevier, 2021)
Introduction: In the absence of specific treatment, preventive strategies are of paramount importance in management of coronavirus disease 2019(COVID-19) pandemic. We estimated cost-effectiveness of non-pharmacological interventions such as hand-hygiene, surgical-mask N-95 respirators and surgical mask in general population. Methods: We performed a decision tree and markov-model based economic evaluation. We estimated total costs and outcomes from public payer's perspective, based on information available through systematic literature search on relative intervention effect during early pandemic phase. We estimated outcomes as number COVID-19 prevented and Quality Adjusted life year (QALY) over one-year time-horizon with one-day cycle-length. Incremental cost effectiveness ratios (ICER) was calculated multiple sensitivity analyses were applied to assess parameter uncertainty. Results: Use of surgical mask with hand hygiene, fit tested N-95 respirator, surgical-mask, non-fit tested N-95 and hand-hygiene interventions prevented additional 1139, 1124, 1121, 1043 and 975 COVID-19 cases per-million as compared to using none. Additional costs incurred (in billion) were ₹29.78 ($0.40), ₹148.09 ($1.99), ₹72.51 ($0.98), ₹26.84 ($0.36) and ₹2.48 ($0.03) as well as additional QALYs gained were 357.4, 353.01, 327.95, 351.52 and 307.04 for surgical mask with hand hygiene, fit-tested N-95, non-fit-tested N-95, surgical mask and hand-hygiene respectively. ICERs with surgical with hand hygiene, hand-hygiene alone, surgical-mask alone, N-95 respirator fit and non-fit test were 83.32($1.12), 8.07($0.11), 76.36($1.03), 419.51($5.65) and 221.10 ($2.98) million ₹ ($)/QALY respectively. Results were robust on uncertainty analysis. Discussion: Among the non-pharmacological interventions to be considered for preventing spread of COVID-19, hand hygiene was cost-effective and avoidance of use of surgical masks and respirators by the general public could save resources.